Forms of adaptation of the social legislation of Ukraine to the EU legislation - Maliuga, Lesya (Київський національний університет імені Тараса Шевченка, 2018)
The forms of adaptation of the social legislation of Ukraine to the EU legislation are revealed in the article. The social legislation as for the nature of each essential form is characterized. The specific character of approximation, implementation, coordination, unification, harmonization as forms of adaptation ofthe Ukrainian social legislation to the EU legislation is given in details. On the basis of this it is stated that the adaptation of the social legislation of Ukraine to the EU legislation is carried out in an active and versatile way.

У статті виявлено форми адаптації соціального законодавства України до законодавства ЄС. Охарактеризовано соціальне законодавство на предмет притаманності кожної із форм. Деталізовано специфіку апроксимації, імплементації, координації, уніфікації, гармонізації як форм адаптації соціального законодавства України до законодавства ЄС. На основі цього констатовано, що адаптація соціального законодавства України до законодавства ЄС здійснюється активно та різносторонньо. Наукове дослідження виконано в рамках держбюджетної теми № 16БФ042-01 «Теорія та практика адаптації законодавства України до законодавства ЄС»
ФОРМИ АДАПТАЦІЇ СОЦІАЛЬНОГО ЗАКОНОДАВСТВА УКРАЇНИ ДО ЗАКОНОДАВСТВА ЄС
Keywords: social legislation; eurointegration; social standards; social rights; social security; forms of adaptation of legislation; соціальне законодавство; євроінтеграція; соціальні стандарти; соцільні права; форми адаптації законодавства